F07. Using ultra-high field 7T MRI for evaluation of EEG findings in patients with temporal lobe epilepsy. (May 2018) - Salehi, Fateme; Kwan, Benjamin; Mirsattari, Seyed M.; Marti, Ana Suller; Lee, Donald; Santyr, Brendan; Burneo, Jorge; Steven, David; Hammond, Robert; Peters, Terry M.; Khan, Ali R.
Abstract : Introduction: Assessment of patients for temporal lobe epilepsy (TLE) surgery requires multimodality input, including anatomical MRI, neuropsychological evaluation, functional neuroimaging, scalp electroencephalography (EEG) and invasive EEG recordings to ensure optimal surgical planning. Often EEG demonstrates abnormal foci that are not detected on 1.5T MRI. Ultra high-field MRI at 7T provides much improved resolution of the brain. We investigated the utility of 7T MRI to detect potential anatomical abnormalities associated with functional abnormalities detected by scalp and/or invasive EEG recordings. Methods: Ultra-high-field data were acquired on a 7T neuroimaging optimized MRI scanner for 13 patients with a history of drug resistant TLE during evaluation for epilepsy surgery. All patients had video-EEG telemetry recordings in our Epilepsy Monitoring Unit. Additionally, 9 patients underwent invasive EEG recordings including subdural and/or depth electrodes. Qualitative evaluation of 7T imaging for scan quality and presence of focal abnormalities detected on EEG was performed. The correlation of 7T MRI findings with EEG recordings of focal slowing or interictal epileptic spikes (IEDs), and seizures was performed. Results: Assessment of 7T MRI demonstrated concordance with the clinically suspected TLE in 8 out of 13 cases. Among these, 3 exhibited supportive abnormal 7T MRI abnormalities not detected by the clinical 1.5T MRI. Eleven out of 13 cases had scalp and/or invasive electrode EEG findings with no anatomic correlates on 1.5T or 7T MRI. Findings included IEDs localizing to the contralateral temporal lobe in 6 patients, frontal lobes in 3 patients, and parieto-occipital lobes in 2 patients. Qualitative assessment of 7T images did not reveal any focal anatomical abnormalities to account for the EEG findings in these patients. Conclusion: To our knowledge, this is the first study to investigate the utility of 7T MRI in combination with scalp and invasive. Qualitative ultra high-field 7T MRI findings show a moderate concordance with clinical data. However, 7T MRI did not reveal focal anatomical findings to account for all the abnormalities detected by the scalp EEG recordings in patients with temporal lobe epilepsy.